Measuring Reactive Oxygen Species in Semen for Male Preconception Care: A Scientist Perspective - Patience E. Castleton; Joshua C. Deluao; David J. Sharkey; Nicole O. McPherson (Antioxidants, 2022)
Oxidative stress and elevated levels of seminal and sperm reactive oxygen species (ROS) may contribute to up to 80% of male infertility diagnosis, with sperm ROS concentrations at fertilization important in the development of a healthy fetus and child. The evaluation of ROS in semen seems promising as a potential diagnostic tool for male infertility and male preconception care with a number of clinically available tests on the market (MiOXSYS, luminol chemiluminescence and OxiSperm). While some of these tests show promise for clinical use, discrepancies in documented decision limits and lack of cohort studies/clinical trials assessing their benefits on fertilization rates, embryo development, pregnancy and live birth rates limit their current clinical utility. In this review, we provide an update on the current techniques used for analyzing semen ROS concentrations clinically, the potential to use of ROS research tools for improving clinical ROS detection in sperm and describe why we believe we are likely still a long way away before semen ROS concentrations might become a mainstream preconception diagnostic test in men.